ANALISIS POTENSI BENCANA GELOMBANG LAUT EKSTRIM DAN ABRASI PANTAI DI WILAYAH PESISIR KABUPATEN PASANGKAYU, SULAWESI BARAT - Imran Kadir (Universitas Sulawesi Barat, 2023)
This study aims to determine the potential for extreme wave disasters and coastal abrasion in the coastal area of ​​Pasangkayu Regency, West Sulawesi Province. This research was carried out with data from various agencies in the Pasangkayu Regency, West Sulawesi. sea ​​wave. Geomorphological and lithological data. Regional population and settlement data. This data was processed using threat, vulnerability, and capacity index analysis using BNPB Regulations No. 1 and No. 2 of 2012. The results showed that at 2.60, the wooden slabs were categorized as high. anal velocity, vegetation cover and shoreline shape. Where the anal velocity factor has the highest weight, which is 30%, while the vegetation cover and the shape of the beach are 15% each. Keywords: Coastal, Wave. Abrasion